2019
DOI: 10.1021/acssuschemeng.8b05681
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Conversion of NaHCO3 into Formate and Simultaneous Synthesis of AlO(OH) from Waste Al-Can in Water

Abstract: Developing a green and highly efficient method for CO 2 reduction into value-added chemicals with earth-abundant materials and facile hydrogen source is crucial to the practical application of CO 2 conversion and utilization. In this study, a new method of reduction of NaHCO 3 , a model compound of CO 2 , to formate as a hydrogen storage material by splitting water with waste Al-can as a reductant is proposed. A formate yield up to 65% from bicarbonate was successfully obtained with waste raw Al-can strips as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Jin and co‐workers reported a new method for reduction of NaHCO 3 to formate as a hydrogen storage system by splitting water with waste aluminum‐can (Al‐can) as a reductant and water as a hydrogen source (Figure 24). [104] The results of hydrothermal reactions showed good formate yield up to 65 % on reduction of bicarbonate by using simple waste Al‐can strips.…”
Section: Effect Of Ph and Temperature On Formate‐bicarbonate Cyclementioning
confidence: 96%
See 2 more Smart Citations
“…Jin and co‐workers reported a new method for reduction of NaHCO 3 to formate as a hydrogen storage system by splitting water with waste aluminum‐can (Al‐can) as a reductant and water as a hydrogen source (Figure 24). [104] The results of hydrothermal reactions showed good formate yield up to 65 % on reduction of bicarbonate by using simple waste Al‐can strips.…”
Section: Effect Of Ph and Temperature On Formate‐bicarbonate Cyclementioning
confidence: 96%
“…Jin and co-workers reported a new method of reduction of NaHCO 3 , to formate as a hydrogen storage material by splitting of H 2 O with waste aluminum-can (Al-Can) as a reductant. [104] The process successfully generated 65 % of formate from bicarbonate using raw Al-can strips and H 2 O as a source of hydrogen. Chemical equation in Figure 30 shows the process involved in bicarbonate reduction using waste Al-Can.…”
Section: Kinetics Of Formate Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fitting results showed that the activation energy of hydrothermal HCO 3 − reduction to formic acid (21 kJ/mol) is much lower than that of the earlier kinetic modelling work on conventional hydrogenation, which needs to overcome the 68 kJ/mol energy barrier. Besides, numerous reports demonstrated that conversion of HCO 3 − to formic acid follows the first‐order reaction model in a wide temperature range from 225 to 375°C 19,51,52,53 …”
Section: Reaction Mechanism Of Hydrothermal Reduction Of Co2 Into For...mentioning
confidence: 99%
“…24 Additionally, FA has potential as a hydrogen storage medium for fuel cell applications. [24][25][26][27][28] At present, a majority of reports focus on the transformation of CO 2 into formate via homogeneous catalytic systems, 15,[29][30][31][32][33] but the recycling and separation issues intrinsically associated with homogeneous catalysts limit their application in large scale. Concerning the production of formate from CO 2 over heterogeneous catalysts, the active elements are dominated by noble metals such as Ru, 16 Au 18 and Pd.…”
Section: Introductionmentioning
confidence: 99%